Analysis of Nitrogen Nutrients in Liquid Organc Fertilizers from Wastewater of Rice Washing and Coconut Husks Mixture - Wardatul Hanifah; Vanny M. A. Tiwow; Ratman Ratman (Universitas Tadulako, 2020)
This study aimed to determine the process of making a liquid organic fertilizer from wastewater of washing rice and coconut husks as well as to determine the amount of nitrogen contained in liquid organic fertilizer. Nitrogen contents were determined using a colorimeter. The results showed that the nutrient content of nitrogen in the liquid organic fertilizer from wastewater of washing rice and coconut husk from fermentation process in a sample of 10 days for a ratio of 1: 3, 1: 1 and 3: 1 was obtained that nitrogen contents were respectively 0.52, 0.41, and 0.20%. The results of fermentation in a sample of 14 days for a ratio of 1: 3, 1: 1 and 3: 1 obtained that nitrogen contents were 0.62, 0.49, and 0.25%.